Conceptual approaches to defining socio-economic protection at the regional level - L. A. Kriventsova (Вестник университета)
The paper examines the applicability of the term “socio-economic protection at the regional level. Since there is a division between economic and social aspects, this term has not yet become widespread. However, considering the close relationship between these aspects, it is important to study socio-economic protection using an integrative approach. The purposes of this research are to formulate the author’s vision of conceptual approaches to defining the socio-economic protection of a region and to construct its conceptual and categorical scheme. The study uses methods of critical analysis and systematisation of published theoretical and applied research by Russian scientists. The results have revealed, on the one hand, the multifactor nature of the concept of the socio-economic protection, and, on the other hand, the existence of general trends in socio-economic development aimed at ensuring the standard and quality of life of the population at the regional level. The author’s substantiation of the conceptual approach to defining the socio-economic protection of a region implies an integrated consideration of this category as achievement of the level of development when the economic state of the region acts as a guarantor of a decent standard of living for the population and availability of sufficient resources to ensure it. The results of the study can be used in the future to develop a methodological apparatus for assessing the level of the socio-economic protection of regions.